Determinan perilaku tes HIV ibu hamil di Puskesmas Bandarharjo Kota Semarang - Rany Ekawati; Yanri Subronto; Mohammad Hakimi (Berita Kedokteran Masyarakat (BKM), 2017)
Determinants of HIV testing behavior among pregnant women in public health center Bandarharjo Semarang PurposeThis research aimed to determine factors associated with HIV testing behavior among pregnant women at the public health center Bandarharjo Semarang.MethodsThis research was a descriptive analytic observational study with a matched case control design. Samples were pregnant women at the health center in Bandarharjo Semarang who have been offered an HIV test totaling 90 samples. Samples in the control group were matched according to trimester age of pregnancy to the case group with ratio of 1:1. Samples were enlisted by consecutive sampling. The research instrument used was a questionnaire. The data analysis consisted of univariable, bivariable comparisons using the McNemar test, and multivariable using conditional logistic regression tests.ResultsNo significant correlations were found, but practical information about HIV (OR 2.35; CI95% 0.801-6.9) and stigma (OR 2.16; CI95% 0.722-6.479) were related to HIV testing behavior.ConclusionPractical information about HIV and stigma are correlated to HIV testing behavior.